2018
DOI: 10.1177/2158244018794775
|View full text |Cite
|
Sign up to set email alerts
|

Making a Case for the Critical Examination of Assignments of Responsibilities in the Reproductive Realm: Insights From South Sudan

Abstract: Drawing on interviews with purposefully selected informants (n = 44) and on focus group discussions (n = 5), this article critically examines and reflects upon the gendered assignments of responsibilities in the reproductive realm, in the context of South Sudan. Through this examination, it provides insight into the social practices of assigning and apportioning responsibilities in the reproductive realm; it exposes the nature of social relations, social positions, and vulnerabilities they signal, and the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Such an approach may also offer opportunities to engage constructively with peer norm processes among girls (adolescents and younger girls). Another important way forward, as detailed in our earlier work [20], would be to engage adolescent boys and men around notions of reproductive responsibility in ways such that they can appreciate the broader societal benefits, and their own 'emancipatory interests' [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an approach may also offer opportunities to engage constructively with peer norm processes among girls (adolescents and younger girls). Another important way forward, as detailed in our earlier work [20], would be to engage adolescent boys and men around notions of reproductive responsibility in ways such that they can appreciate the broader societal benefits, and their own 'emancipatory interests' [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The project was implemented between 2012 and 2016 and was geared towards supporting the State Ministries of Health of three states (including WBeG) to improve the quality and responsiveness of the sexual and reproductive health services. Findings from research done amongst adults have been reported earlier [17][18][19][20]. Insights from this research, particularly about how social norms and gender relations shape women's sexual and reproductive health in South Sudan, have also extensively informed this inquiry; it particularly helped us to develop the interview questions and to locate the analysis in the broader social context of the study community.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation